Pengaruh Ukuran Perusahaan, Struktur Modal, Likuiditas, dan Profitabilitas terhadap Kualitas Laba - Shofa Zulfriza Yuliana; Fitri Ella Fauziah (Jurusan Akuntansi Politeknik Negeri Pontianak, 2022)
Earnings quality is a benchmark for stakeholders in determining the decisions to be taken. The purpose of this study is to determine and analyze company size, capital structure, liquidity and profitability on earnings quality. This study uses consumer goods companies as research samples. The analytical tool used is multiple regression. The results showed that firm size, capital structure, and liquidity had no effect on earnings quality, while profitability had a negative effect on earnings quality.